Approaches for Mainstreaming Biodiversity into the Forestry Sector - Thomson Jacob, C.; Kinhal, Giridhar (Indian Forester, 2021)
Forests are a dynamic natural resource. They offer a diverse set of habitats for plants, animals, and micro-organisms and hold the majority of the world's terrestrial species. However, these biologically rich systems are increasingly threatened, largely as a result of human activities. The Food and Agriculture Organization of the United Nations has estimated that since 1990 world has lost nearly 178 million ha. of forest. India is rich in biodiversity and it supports 49,003 species of plants and 1,00,693 species of animals and it ropes 16% of the human and 18% of the cattle population of the world. India's forest diversity includes 3794 trees, 3111 shrubs, and 2300 herbs. The forest cover of India constitutes 21.67 per cent of the geographic area of the country and nearly 1,70,000 villages are deriving benefits from the forests. The Convention on Biological Diversity has requested parties to address the loss of biodiversity through its global strategic plan for biodiversity and to mainstream biodiversity into all sectors. Some of the suggested approaches for mainstreaming biodiversity into the forestry sector include policy intervention; convergence of national and international instruments; multi-sectoral management and local institutional partnerships.